THE INFLUENCE OF LITERACY FINANCE AND FINANCIAL TECHNOLOGY ON INCLUSION FINANCE FOR SMALL AND MEDIUM ENTERPRISE (SMEs) ACTORS IN TERNATE CITY - Adinda Iskandar; Abdul Hadi Sirat; Muhsin N. Bailusy (Journal of Management and Islamic Finance, 2023)
This research aims to analyze the role of financial literacy and financial technology on the financial inclusion of SMEs in Ternate. By applying a purposive sampling method, the number of samples used in this research were 50 SMEs engaged in the food industry. This research was carried out by using data analysis assisted by SPSS 25 software. The results of the research show that: (1) financial literacy has a significant effect on the financial inclusion of SMEs in Ternate City, meaning that the better the financial literacy implemented, the more financial inclusion behavior it will get better in certain businesses; (2) financial technology has a significant effect on the financial inclusion of SMEs in Ternate City. Financial literacy aids individuals in developing skills for managing personal finances. A thorough comprehension of budget creation, expense control, and savings can enhance a person's financial wellness. Financial literacy reduces financial uncertainty by providing knowledge about risks and ways to manage them. Additionally, fintech, or financial technology, contributes significantly to increasing financial inclusion.